2022
DOI: 10.1002/anie.202212726
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Assembly and Three‐Dimensional Stacking of Antiaromatic 5,15‐Dioxaporphyrin on HOPG

Abstract: Antiaromatic compounds have recently received considerable attention because of their novel properties such as narrow HOMO-LUMO gaps and facile formation of mutual stacking. Here, the spontaneous assembly of antiaromatic meso-2-thienyl-substituted 5,15-dioxaporphyrin (DOP-1) is scrutinized at the liquid-solid interface by scanning tunneling microscopy (STM). Polymorphism in monolayers characterized by the orthogonal and parallel assemblies is found at the low concentration of 0.05 mM. The parallel assembly is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Molecular manipulation of sandwich doubledecked complexes and construction of assemblies at the liquidsolid interface can also be achieved by STM analysis. [131,132] Small 2023, 19, 2300413 [126] Copyright 2022, Wiley-VCH. b) Reproduced with permission.…”
Section: Nonplanar Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular manipulation of sandwich doubledecked complexes and construction of assemblies at the liquidsolid interface can also be achieved by STM analysis. [131,132] Small 2023, 19, 2300413 [126] Copyright 2022, Wiley-VCH. b) Reproduced with permission.…”
Section: Nonplanar Moleculesmentioning
confidence: 99%
“…b-3) Small-scale STM images and energy-minimized clockwise structure of the bilayer arrangement of (L)-FAC18. a) Reproduced with permission [126]. Copyright 2022, Wiley-VCH.…”
mentioning
confidence: 99%
“…In a recent study by Shimizu et al , the spontaneous assembly of 111 (Ar = 2-thienyl) was studied at the liquid–solid interface to elucidate its polymorphism in a monolayer and the facile formation of the stacked layer. 77…”
Section: Synthesis Of 515-dioxa- and 515-dithia-porphyrinoidsmentioning
confidence: 99%
“…Theoretical studies have also shown that orbital switching occurs when the π-stacking distance of Ni(II) norcorrole face-to-face stacking is reduced to 3.0 Å . On the other hand, scanning tunneling spectroscopy shows that the HOMO–LUMO gap of the bilayers in antiaromatic meso -2-thioethyl-substituted 5,15-dioxaporphyrin is smaller than that of monolayers (Scheme b) . These results show different properties, although the antiaromatic molecules are stacked.…”
Section: Introductionmentioning
confidence: 99%
“…26 On the other hand, scanning tunneling spectroscopy shows that the HOMO−LUMO gap of the bilayers in antiaromatic meso-2-thioethyl-substituted 5,15-dioxaporphyrin is smaller than that of monolayers (Scheme 1b). 27 These By focusing on the π-stacking distance and the change in molecular orbitals, it might be possible to clarify whether stacking aromatization occurs or not. In this study, we investigated the changes in aromaticity and molecular orbitals for fully stacked dimer models with cyclobutadiene, which is the simplest antiaromatic molecule, and we adopted density functional theory (DFT) 28,29 calculations.…”
Section: Introductionmentioning
confidence: 99%